First to file, Trademark squatting, Fairness, Famous Marks and Law Reform. - Nathania, Michelle (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Trademark protection in Indonesia is regulated under the first to file system, in which rights to a trademark are granted to the party who first registers it at the Directorate General of Intellectual Property (DJKI). Although this system provides legal certainty, its application often leads to injustice, especially in the case of trademark squatting, where a party who is not in good faith registers a mark that has been recognized by another party with the aim of obtaining profits. This research aims to analyze the application of the first to file principle in trademark registration in Indonesia from the perspective of justice, as well as evaluate the legal measures that can be applied to prevent abuse of this system. This research uses the normative juridical method with the analysis of primary, secondary, and tertiary legal materials, as well as John Rawls' theory of justice approach as the basis for policy evaluation. The results show that weaknesses in the definition of good faith, the criteria for famous marks, and the limitation of similarities in essence cause legal uncertainty and open loopholes for abuse. Policy reform is needed through improving the legal substance, strengthening the institutional structure of the DJKI, and simplifying the dispute resolution mechanism through mediation and arbitration. The research conclusions emphasize the importance of more inclusive and equitable legal reforms to protect the rights of legitimate trademark owners, especially small and medium enterprises. With proper legal reform, it is expected that the trademark protection system in Indonesia can become more transparent, effective, and contribute to fair business competition.